2018
DOI: 10.3390/ijerph15092031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Its Associated Factors among Vegetarians in Malaysia

Abstract: The prevalence and factors associated with metabolic syndrome (MetS) remain unknown in Malaysian vegetarians. This cross-sectional study aimed to determine the prevalence of MetS among vegetarians in Kuala Lumpur and Selangor and its associated factors. The data on socio-demographic characteristics, vegetarianism practises, lifestyle behaviours, body weight, height, waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood glucose (FBG), and blood lipid profiles wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 46 publications
(74 reference statements)
4
24
0
Order By: Relevance
“…Similar to the ndings of previous research, this study reported signi cant links between MetS and increased body weight [60,62,63], waist circumference [63][64][65], body fat percentage [63,64] and BMI [9], except for total cholesterol level or LDL-c level. However, the ndings revealed that MetS status is independent of sociodemographic and clinical characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the ndings of previous research, this study reported signi cant links between MetS and increased body weight [60,62,63], waist circumference [63][64][65], body fat percentage [63,64] and BMI [9], except for total cholesterol level or LDL-c level. However, the ndings revealed that MetS status is independent of sociodemographic and clinical characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the findings of previous research, this study reported significant links between MetS and increased body weight (Ching et al 2018;Moreira et al 2014;Ortiz-Rodríguez et al 2017), waist circumference (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017;Raposo et al 2017), body fat percentage (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017) and BMI (Wu et al 2018). However, we did not find a significant difference across MetS status in any specific sociodemographic profile, total cholesterol level or LDL-c level.…”
Section: Contrarilysupporting
confidence: 90%
“…Meanwhile, previous literatures have described the links between MetS and other sociodemographic and lifestyle factors among Malaysian adults, such as higher age, unemployment, working in shifts, postmenopausal status, living in urban area, lower socioeconomic status, Indian ethnicity, Chinese ethnicity and lower education level (Kiew et al 2018;Jan Mohamed et al 2013;Ching et al 2018;Mohamud et al 2011;Rampal et al 2012;Lim and Cheah 2016;Ramli et al 2013;Tan, Dunn, and Yen 2011). Specifically, these factors can be linked with other modifiable risk factors of MetS such as physical inactivity and unhealthy diets.…”
Section: Contrarilymentioning
confidence: 99%
“…Furthermore Kaur et al, reported that the odds of MetS among Malaysian Punjabis (Indians) were higher with primary education, compared to those with higher education levels [43]. Ching et al, however, have reported that higher education levels of Malaysian vegetarians with and without MetS were observed to be nearly the same [44]. This could be due to the fact that it was a unique group of subjects with specific dietary habits and the results pertaining to this group may not represent the general population of Malaysia.…”
Section: Discussionmentioning
confidence: 99%